Increased BBB Permeability Enhances Activation of Microglia and Exacerbates Loss of Dendritic Spines After Transient Global Cerebral Ischemia - Ju, Furong; Ran, Yanli; Zhu, Lirui; Cheng, Xiaofeng; Gao, Hao; Xi, Xiaoxia; Yang, Zhanli; Zhang, Shengxiang (Frontiers in Cellular Neuroscience, 2018)
Abstract Ischemic stroke can induce rapid disruption of blood–brain barrier (BBB). It has been suggested that increased BBB permeability can affect the pathological progression of ischemic tissue. However, the impact of increased BBB permeability on microglial activation and synaptic structures following reperfusion after ischemia remains unclear. In this study, we investigated microglial activation, dendritic damage and plasticity of dendritic spines after increasing BBB permeability following transient global cerebral ischemia in the somatosensory cortices in mice. Bilateral common carotid artery ligation (BCAL) was used to induce transient global cerebral ischemia. Mannitol was used to increase the BBB permeability. Intravital two-photon imaging was performed to image the dendritic structures and BBB extravasation. Microglial morphology was quantitated using a skeletonization analysis method. To evaluate inflammation of cerebral cortex, the mRNA expression levels of CD11b, CD68, IP10 and TNF-α were measured by fluorescent quantitative PCR. Intravital two-photon imaging revealed that mannitol caused a drastic increase in BBB extravasation during reperfusion after transient global ischemia. Increased BBB permeability induced by mannitol had no significant effect on inflammation and dendritic spines in healthy mice, but triggered a marked de-ramification of microglia; importantly, in ischemic animals, mannitol accelerated de-ramification of microglia and aggravated inflammation at 3 h but not at 3 days following reperfusion after ischemia. Although mannitol did not cause significant change in the percentage of blebbed dendrites and did not affect the reversible recovery of the dendritic structures, excessive extravasation was accompanied with significant decrease in spine formation and increase in spine elimination during reperfusion in ischemic mice. These findings suggest that increased BBB permeability induced by mannitol can lead to acute activation of microglia and cause excessive loss of dendritic spines after transient global cerebral ischemia